Consciousness, unconsciousness and death in the context of slaughter. Part I. Neurobiological mechanisms underlying stunning and killing. (August 2016) - Terlouw, Claudia; Bourguet, Cécile; Deiss, Véronique
Abstract: This review describes the neurobiological mechanisms that are relevant for the stunning and killing process of animals in the abattoir. The mechanisms underlying the loss of consciousness depend on the technique used: mechanical, electrical or gas stunning. Direct exsanguination (without prior stun) causes also a loss of consciousness before inducing death. The underlying mechanisms may involve cerebral anoxia or ischemia, or the depolarisation, acidification and/or the destruction of brain neurons. These effects may be caused by shock waves, electrical fields, the reduction or arrest of the cerebral blood circulation, increased levels of CO2 or low levels of O2 in the inhaled air, or the mechanical destruction of neurons. The targeted brain structures are the reticular formation, the ascending reticular activating system or thalamus, or the cerebral hemispheres in a general manner. Some of the techniques, when properly used, induce an immediate loss of consciousness; other techniques a progressive loss of consciousness. Highlights: Stunning techniques use various principles to disturb normal brain function. Most techniques involve mechanical destruction, acidification or depolarisation of neurons. Targets are the reticular formation, its projections, or the cerebral hemispheres. Death is caused by cerebral anoxia/ischemia or the destruction of brain neurons.